Practicing Mindfulness in an Elementary School Workplace - Catherine Joan G. Violago; Isabel Pefianco Martin (Indonesian Journal of Educational Research and Technology, 2024)
Teachers, administrators, and staff members deal with a variety of challenges and demands daily in elementary schools. Multiple factors may contribute to the increase in stress levels, burnout, and emotional exhaustion. Some examples of these include the heavy workload, student engagement and management, and the need to uphold academic standards. In the hopes of addressing the global learning crisis, institutions must invest and provide different types of support for their educators. Schools need to assess the mental well-being of their teachers amidst the transitions made during the pandemic. Hence, the importance of this study is to understand the teacher’s motivation to improve students’ learning outcomes. Many ways in which mindfulness affected teachers' well-being were significant. Participants had a better understanding of their motivations, which helped them feel more connected to their teaching goals. Practices of mindfulness helped people adopt the attitude of embracing intrinsic rewards, which improved their motivation overall. The mindfulness integration within the school environment also contributed to a positive shift in the teacher community, fostering a culture of empathy, support, and collaboration. The study's implications extend to educational policy and practice, demonstrating the potential advantages of incorporating mindfulness to build a strong and empowered teaching community, eventually generating a richer learning environment for students.